CHOOSING AUTHENTIC READING MATERIALS FOR LESSONS AT HIGHER SCHOOLS IN UZBEKISTAN (Conferencea, 2022)
Learning a foreign language is one of the most pressing issues of the evolving era today. Because by knowing the language, people will be able to communicate and exchange information. It is also possible to update the experience through data exchange and also to discover a new lifestyle. This lifestyle can be beneficial for all of humanity. Today in our country the attention and demand for learning and teaching a foreign language is growing day by day. Cooperation has been established with many developed and developing foreign countries, and as a result, the study of not only English but also other foreign languages has been radically reformed.